Identification of Cancer Stem Cell Subpopulations in Head and Neck Metastatic Malignant Melanoma - Vithushiya Yoganandarajah; Josie Patel; Bede van Schaijik; Nicholas Bockett; Helen D. Brasch; Erin Paterson; Dalice Sim; Paul F. Davis; Imogen M. Roth; Tinte Itinteang; Swee T. Tan (Cells, 2020)
Cancer stem cells (CSCs) have been identified in many cancer types. This study identified and characterized CSCs in head and neck metastatic malignant melanoma (HNmMM) to regional lymph nodes using induced pluripotent stem cell (iPSC) markers. Immunohistochemical (IHC) staining performed on 20 HNmMM tissue samples demonstrated expression of iPSC markers OCT4, SOX2, KLF4, and c-MYC in all samples, while NANOG was expressed at low levels in two samples. Immunofluorescence (IF) staining demonstrated an OCT4+/SOX2+/KLF4+/c-MYC+ CSC subpopulation within the tumor nests (TNs) and another within the peritumoral stroma (PTS) of HNmMM tissues. IF also showed expression of NANOG by some OCT4+/SOX2+/KLF4+/c-MYC+ cells within the TNs in an HNmMM tissue sample that expressed NANOG on IHC staining. In situ hybridization (n = 6) and reverse-transcription quantitative polymerase chain reaction (n = 5) on the HNmMM samples confirmed expression of all five iPSC markers. Western blotting of primary cell lines derived from four of the 20 HNmMM tissue samples showed expression of SOX2, KLF4, and c-MYC but not OCT4 and NANOG, and three of these cell lines formed tumorspheres in vitro. We demonstrate the presence of two putative CSC subpopulations within HNmMM, which may be a novel therapeutic target in the treatment of this aggressive cancer.